Design, Synthesis, and Evaluation of 2-Amino-6-nitrobenzothiazole-Derived Hydrazones as MAO Inhibitors: Role of the Methylene Spacer Group - Tripathi R.K.P.; Ayyannan S.R. (My University, 2025)
A series of 2-amino-6-nitrobenzothiazole-derived extended hydrazones were designed, synthesized, and investigated for their ability to inhibit monoamine oxidase A and B (MAO-A/MAO-B). The compounds were found to exhibit inhibitory activities in the nanomolar to micromolar range. Some of the compounds showed excellent potency and selectivity against the MAO-B isoform. N′-(5-Chloro-2-oxoindolin-3-ylidene)-2-(6-nitrobenzothiazol-2-ylamino)acetohydrazide (compound 31) showed the highest MAO-B inhibitory activity (IC50=1.8±0.3 nm, selectivity index [SI]=766.67), whereas compound 6 [N′-(1-(4-bromophenyl)ethylidene)-2-(6-nitrobenzothiazol-2-ylamino)acetohydrazide] was found to be the most active MAO-A inhibitor (IC50=0.42±0.003 μm). Kinetic studies revealed that compounds 6 and 31 exhibit competitive-type reversible inhibition against both MAO-A and MAO-B, respectively. Structure–activity relationship (SAR) studies disclosed several structural aspects significant for potency and the contribution of the methylene spacer toward MAO-B inhibitory potency, with minimal or no neurotoxicity. Molecular modeling studies yielded a good correlation between experimental and theoretical inhibitory data. Binding pose analysis revealed the significance of cumulative effects of π–π stacking and hydrogen bond interactions for effective stabilization of virtual ligand–protein complexes. Further optimization studies of compound 31, including co-crystallization of inhibitor–MAO-B complexes, are essential to develop these compounds as potential therapeutic agents for MAO-B-associated neurodegenerative diseases. © 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim